Multi‐shot acquisitions for stimulus‐evoked spinal cord BOLD fMRI. Issue 4 (10th November 2020) - Barry, Robert L.; Conrad, Benjamin N.; Maki, Satoshi; Watchmaker, Jennifer M.; McKeithan, Lydia J.; Box, Bailey A.; Weinberg, Quinn R.; Smith, Seth A.; Gore, John C.
Abstract : Purpose: To demonstrate the feasibility of 3D multi‐shot magnetic resonance imaging acquisitions for stimulus‐evoked blood oxygenation level dependent (BOLD) functional magnetic resonance imaging (fMRI) in the human spinal cord in vivo. Methods: Two fMRI studies were performed at 3T. The first study was a hypercapnic gas challenge where data were acquired from healthy volunteers using a multi‐shot 3D fast field echo (FFE) sequence as well as single‐shot multi‐slice echo‐planar imaging (EPI). In the second study, another cohort of healthy volunteers performed an upper extremity motor task while fMRI data were acquired using a 3D multi‐shot acquisition. Results: Both 2D‐EPI and 3D‐FFE were shown to be sensitive to BOLD signal changes in the cervical spinal cord, and had comparable contrast‐to‐noise ratios in gray matter. FFE exhibited much less signal drop‐out and weaker geometric distortions compared to EPI. In the motor paradigm study, the mean number of active voxels was highest in the ventral gray matter horns ipsilateral to the side of the task and at the spinal level associated with innervation of finger extensors. Conclusions: Highly multi‐shot acquisition sequences such as 3D‐FFE are well suited for stimulus‐evoked spinal cord BOLD fMRI.